Family displacement during syriab crisis and its effect on the educational level of children (field study on the displaced families in AlQutaifa city) - Trkia, Bahaa; Arbash, Siba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to knowing to the families displaced and its impact on educational level. , it aimed at recognizing difficulties that suffered by the children of displaced families in learning and the reason for are not joining in AL-Qutaifa schools, a questionnaire was adopted (designed) as a tool to collect information , and it was distributed on a sample of (50) displaced families in AL-Qutaifa city in Damascus countryside. The study came to many results including: "the impact of each of the educational level of the father and the mother and the work of the head of household, economic level of household, and work of the displaced children" on the impact on the children of displaced families towards education Finally , it was ended up to several recommendations.